Potential missing steps for a wide use of dried matrix spots in biomedical analysis. (September 2015) - Déglon, Julien; Leuthold, Luc Alexis; Thomas, Aurélien
Microsampling, mainly as DBS, has been significantly expanded in the biomedical and pharmaceutical communities in the last 10 years. In parallel, technology and methodology have evolved to overcome some of the issues associated with this sampling procedure. Despite the continuous developments and interest, only a few validated and routinely implemented clinical applications have arisen beyond the initial inborn screening. Based on the latest developments in this field, this perspective aims to discuss some of the missing steps (i.e., the habits to change, the Health Authorities acceptance and the shift for dried plasma generation), which may turn the current use of microsampling into an established and standard procedure in clinical and pharmaceutical analysis.